2021
DOI: 10.1021/acsami.1c17642
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Tumor Microenvironment-Activated Multifunctional Nanoplatform Coupled with Turn-on and Always-on Fluorescence Probes for Imaging-Guided Cancer Treatment

Abstract: Intrinsic tumor microenvironment (TME)-related therapeutic resistance and nontumor-specific imaging have limited the application of imaging-guided cancer therapy. Herein, a TME-responsive MnO2-based nanoplatform coupled with turn-on and always-on fluorescence probes was designed through a facile biomineralization method for imaging-guided photodynamic/chemodynamic/photothermal therapy (PDT/CDT/PTT). After the tumor-targeting delivery of the AuNCs@MnO2-ICG@AS1411 (AMIT) nanoplatform via aptamer AS1411, the TME-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…The multifunctional nanoparticles are introduced with light/heat/physical dynamics for cancer therapy with synergistic therapy. [455][456][457] For example, Sun et al 458 constructed a multifunctional nanoplatform (AMIT) based on Au nanoclusters (AuNCs) coated with MnO 2 to codeliver ICG and the aptamer AS141 for targeting and image-guided PDT/CDT/PTT (Figure 5). The TME-responsive dissociation of MnO 2 could produce O 2 to enhance ICG-guided PDT and produce Mn 2+ for Fentonlike reaction-mediated CDT.…”
Section: Synergistic Therapymentioning
confidence: 99%
“…The multifunctional nanoparticles are introduced with light/heat/physical dynamics for cancer therapy with synergistic therapy. [455][456][457] For example, Sun et al 458 constructed a multifunctional nanoplatform (AMIT) based on Au nanoclusters (AuNCs) coated with MnO 2 to codeliver ICG and the aptamer AS141 for targeting and image-guided PDT/CDT/PTT (Figure 5). The TME-responsive dissociation of MnO 2 could produce O 2 to enhance ICG-guided PDT and produce Mn 2+ for Fentonlike reaction-mediated CDT.…”
Section: Synergistic Therapymentioning
confidence: 99%
“…Sun et al . reported a multimodal nanoprobe that utilizes the TME for triple therapeutic effect through PDT, chemodynamic therapy and PTT with MRI and fluorescent imaging capabilities 189 . The AS1411 targeted probe consisting of gold nanocluster and ICG encapsulated by MnO 2 , is able to produce O 2 in the H 2 O 2 -rich TME and releases its content through GSH-mediated degradation.…”
Section: Aptamers For Theranostic Applicationsmentioning
confidence: 99%
“…Recently, an intelligent multifunctional nanoplatform was constructed via a simple and green BSA‐mediated biomineralization synthesis method for TME activatable imaging‐guided PDT, CDT, and PTT. [ 169 ] The in vitro and in vivo experimental results showed that the combined effect of the nanocomposite triggered by MnO 2 caused a high tumor inhibition performance, and achieved the fluorescence, magnetic resonance, and photothermal imaging at the same time. In a newly assembled PdH@MnO 2 /Ce6@HA (PHMCH) yolk–shell nanoplatform, [ 170 ] the PdH tetrahedron has a highly efficient hydrogen release behavior controlled by NIR and a significant photothermal effect.…”
Section: Cancer Treatmentmentioning
confidence: 99%